Detection of candidate polymorphisms around the QTL for fat area ratio to rib eye area on BTA7 using whole‐genome resequencing in Japanese Black cattle. (14th January 2020) - Sasazaki, Shinji; Kawaguchi, Fuki; Nakajima, Ayaka; Yamamoto, Raito; Akiyama, Takayuki; Kohama, Namiko; Yoshida, Emi; Kobayashi, Eiji; Honda, Takeshi; Oyama, Kenji; Mannen, Hideyuki
Abstract: In our previous study, we performed genome‐wide association study (GWAS) to identify the genomic region associated with Fat area ratio to rib eye area (FAR) and detected a candidate in BTA7 at 10–30 Mbp. The present study aims to comprehensively detect all polymorphisms in the candidate region using whole‐genome resequencing data. Based on whole‐genome resequencing of eight animals, we detected 127, 090 polymorphisms within the region. Of these, 31, 945 were located within the genes. We further narrowed the polymorphisms to 6, 044 with more than five allele differences between the high and low FAR groups that were located within 179 genes. We subsequently investigated the functions of these genes and selected 170 polymorphisms in eight genes as possible candidate polymorphisms. We focused on SLC27A6 K81M as a putative candidate polymorphism. We genotyped the SNP in a Japanese Black population ( n  = 904) to investigate the effect on FAR. Analysis of variance revealed that SLC27A6 K81M had a lower p‐value ( p  = .0009) than the most significant SNP in GWAS ( p  = .0049). Although only SLC27A6 K81M was verified in the present study, subsequent verification of the remaining candidate genes and polymorphisms could lead to the identification of genes and polymorphisms responsible for FAR.